2023
DOI: 10.3390/v15020536
|View full text |Cite
|
Sign up to set email alerts
|

Game Birds Can Act as Intermediaries of Virulent Genotype VII Avian Orthoavulavirus-1 between Wild Birds and Domestic Poultry

Abstract: Newcastle Disease (ND), caused by virulent forms of Avian orthoavulavirus serotype-1 (AOAV-1) is an economically important avian disease worldwide. The past two incursions of ND into the United Kingdom occurred in game bird populations during 2005 and 2006. The nature of the game bird semi-feral rearing system, which can bring these birds into close contact with both wild birds and commercial or backyard poultry, has been hypothesized to act as a bridge between these two environments. As such, the risk that AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The gene loss in the ruff (Calidris pugnax) is consistent with the Charadriiformes order being the second most important maintenance host after anseriform birds [86,[94][95][96][97]. Although the role of non-Anseriformes and non-Charadriiformes (NANC) species in acting as a reservoir for the influenza virus is difficult to evaluate using current monitoring practices, gamebirds have received considerable attention [98][99][100][101]. Nonetheless, two more species with gene loss, the Anna's Hummingbird (Calypte anna) and the rifleman (Acanthisitta chloris), can be infected by the avian poxvirus and the zoonotic bacterium Chlamydia psittaci, respectively [102][103][104][105].…”
Section: Discussionmentioning
confidence: 82%
“…The gene loss in the ruff (Calidris pugnax) is consistent with the Charadriiformes order being the second most important maintenance host after anseriform birds [86,[94][95][96][97]. Although the role of non-Anseriformes and non-Charadriiformes (NANC) species in acting as a reservoir for the influenza virus is difficult to evaluate using current monitoring practices, gamebirds have received considerable attention [98][99][100][101]. Nonetheless, two more species with gene loss, the Anna's Hummingbird (Calypte anna) and the rifleman (Acanthisitta chloris), can be infected by the avian poxvirus and the zoonotic bacterium Chlamydia psittaci, respectively [102][103][104][105].…”
Section: Discussionmentioning
confidence: 82%
“…Some wild birds may act as intermediate hosts, serving as a bridge for pathogen transmission between wild birds and domestic poultry. Both high and low pathogenic strains of Newcastle disease virus could be detected in wild birds ( Shchelkanov et al, 2006 ; Bansal et al, 2022 ), and pheasants and partridges might serve as intermediate host ( Ross et al, 2023 ). Naggar's study found that there might be 2-way spil-over between wild birds and poultry.…”
Section: Discussionmentioning
confidence: 99%
“…The gene loss in the ruff ( Calidris pugnax ) is consistent with the Charadriiformes order being the second most important maintenance host after anseriform birds [ 97 , 106 109 ]. Although the role of non-Anseriformes and non-Charadriiformes (NANC) species in acting as a reservoir for the influenza virus is difficult to evaluate using current monitoring practices, gamebirds have received considerable attention [ 110 113 ]. Nonetheless, two more species with gene loss, the Anna's hummingbird ( Calypte anna ) and the rifleman ( Acanthisitta chloris ), can be infected by the avian poxvirus and the zoonotic bacterium Chlamydia psittaci , respectively [ 114 117 ].…”
Section: Discussionmentioning
confidence: 99%